Gadyakabitā o tāra bibartana, Rabīndranātha o tāmra uttarasūribrnda - Gupta, Sushil Kumar, 1928- (Saṃskrta Pustaka Bhāṇḍāra, 1978)
Historical study of the Bengali modern poems by Rabindranath Tagore, 1861-1941, and his successors.